Correction method of measured images of absorbed dose for quenching effects due to relatively high LET. (November 2017) - Gambarini, G.; Bettega, D.; Camoni, G.; Felisi, M.; Gebbia, A.; Massari, E.; Regazzoni, V.; Veronese, I.; Giove, D.; Mirandola, A.; Ciocca, M.
Abstract: The quenching of sensitivity of gafchromic films EBT3 with increasing radiation LET is studied and a proposed method for correcting the measured dose images is described. The method evaluates a correction coefficient in each position of the acquired image by multiplying the measured dose value for a calculated ratio of the absorbed dose to the measured one. Such calculated doses are obtained utilising knowledge about absorbed and measured doses for single Bragg peaks from protons of a generic energy E . This topic is under study and the software in MATLAB developed for achieving the correction of the measured images is continuously implemented. The first results to test the validity of the proposed method also for complex dose distributions are promising. Highlights: Radiochromic EBT3 film response decreases with increasing radiation LET. This sensitivity quenching is studied for proton beams of various energies. A method for correcting the dose images acquired with EBT3 films is proposed. Software for possible application in proton therapy practice is developed. Preliminary results show the validity of the proposed method.